A Novel Segmentation Technique to Extract Amygalada of Brain to Detect Insomnia Disorder Using Graph Cut Method - Subhulakshmi, R (International Journal of Computer Sciences and Engineering, 2025)
Insomnia is one of the most dangerous sleepless disorders and can continue through the teenage years and lifelong of human being. This research work focuses on one of the major problems of this disorder happen in human brain called amygalada abnormality. The size and growth of the amygalada will decide the insomnia disorder. Various existing research works to extract the amygalada (Head and body) are surveyed in this thesis and an automatic diagnosis technique is proposed to extract the amygalada in MRI brain images. In the proposed method, Graph Cut Method is used to make it suitable for segmenting small, low contrast structure such as the amygalada to predicting the Insomnia Disorder. The results show accurate and very fast performances in external amygalada segmentation in a real data set.